Meta-Analysis the Effect of Aquatic Therapy on Functional Ability in Patients with Knee Osteoarthritis - Puspita, Wita Hana; Tamtomo, Didik Gunawan; Prasetya, Hanung (Indonesian Journal of Medicine, 2022)
Background: Knee OA can affect mobility in the elderly causing pain and impaired functional ability. This study aims to analyze the effect of aquatic therapy on functional ability in knee osteoarthritis patients based on the results of a number of previous primary studies..Subject and Method: This study was conducted using a meta-analysis method with articles searched using the search keywords "knee osteoarthritis" OR "osteoarthritis genu" AND "aquatic therapy" OR "hydrotherapy" OR "water exercise" AND "functional ability" OR "WOMAC" AND "Randomized Controlled Trial” OR “RCT” from PubMed, google scholar and science direct and processed using RevMan 5.3.Results: 9 RCT articles that fit into the inclusion criteria, with a total of 573 samples. Knee OA patients receiving aquatic therapy had a mean WOMAC score of 1.22 units lower than those without aquatic therapy, and the effect was statistically significant (SMD = -1.22; 95% CI -2.03 to -0.41; p = 0.003). In other words, aquatic therapy is effective in improving functional ability in knee OA patients.Conclusion: Aquatic therapy has an effect on increasing functional ability in knee osteoarthritis patients.Keywords: Osteoarthritis, aquatic therapy, WOMAC indexCorrespondence: Wita Hana Puspita. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: wita.tj0408@gmail.com. Mobile: +628164837959.Indonesian Journal of Medicine (2022), 07(02): 138-149https://doi.org/10.26911/theijmed.2022.07.02.03